Enhanced uptake of blood coagulation factor VIII containing immune complexes by antigen presenting cells. (19th January 2017) - Hartholt, R. B.; Wroblewska, A.; Herczenik, E.; Peyron, I.; ten Brinke, A.; Rispens, T.; Nolte, M. A.; Slot, E.; Claassens, J. W.; Nimmerjahn, F.; Verbeek, J. S.; Voorberg, J.
Abstract : Essentials Anti‐factor (F) VIII antibody formation is a major complication in the treatment of hemophilia A. We investigated uptake of FVIII and FVIII immune complex by bone marrow derived dendritic cells. Immune complex formation increased uptake of FVIII 3‐4 fold in a Fcγ receptor dependent manner. FVIII immune complex binding to Fcγ receptors may modulate immune tolerance induction. Summary: Background: A major complication in the treatment of hemophilia A is the development of inhibitory antibodies targeting coagulation factor VIII (FVIII). Eradication of these inhibitors can be established by immune tolerance induction (ITI), which consists of daily administration of high dosages of FVIII. FVIII immune complexes (FVIII‐IC) could be formed following FVIII infusion in patients with pre‐existing anti‐FVIII antibodies. Objectives: Here we studied endocytosis of FVIII‐IC by bone marrow‐derived dendritic cells (BMDCs). Methods: BMDCs were pulsed with FVIII/FVIII‐IC and uptake was assessed by flow cytometry and confocal imaging. Results: BMDCs were able to efficiently internalize FVIII‐IC in a dose‐dependent manner, 3–4‐fold more efficiently when compared with equimolar concentrations of non‐complexed FVIII. Uptake of FVIII‐IC, but not FVIII alone, could be inhibited with anti‐Fcγ receptor (FcγR) antibody 2.4G2, indicating functional involvement of FcγR. No internalization of FVIII‐IC was observed in BMDCs lacking FcγRI, FcγRIIb, FcγRIII and FcγRIV. Genetic ablation of FcγRIIb, FcγRIII or FcγRIV individually did not affect the ability of anti‐FVIII IgG to promote the uptake of FVIII. BMDCs lacking FcγRI showed lower FVIII‐IC uptake levels when compared with other single FcγR null BMDCs. Expression of the inhibitory FcγRIIb alone was sufficient to internalize FVIII‐IC more efficiently than FVIII. Conclusions: FcγR are critical in the internalization of FVIII‐IC by BMDCs and multiple FcγR can contribute independently to this process. Our findings provide a basis for future studies to address whether the outcome of ITI is dependent on the interplay between FVIII‐IC and inhibitory and activating FcγR.